Design, synthesis and antiproliferative activity of novel colchicine derivatives: selective inhibition of melanoma cell proliferation - Kumar, Puneet; Kotra, Tusharika; Lone, Waseem I.; Arfath, Yassir; Tiwari, Harshita; Shukla, Ashutosh Kumar; Ahmed, Zabeer; Rayees, Sheikh; Anal, Jasha Momo H. (Frontiers in Pharmacology, 2025)
Colchicine binds to tubulin and destabilizes microtubules, stopping cell division and causing apoptosis. Its anti-cancer property affects microtubule integrity despite its reported toxicity. A series of novel colchicine derivatives were synthesized using the multi-component reaction method and evaluated for their antiproliferative properties, aiming to enhance their efficacy as anti-cancer agents compared to the parent compound, colchicine. With the SRB assay, we tested these derivatives for their anti-cancer efficacy against lung, breast, and melanoma using several human cancer cell lines, including A549, MCF-7, MDAMB-231, and A375. The study identified a derivative, 3g, as notably more effective against melanoma cells, with a selectivity index about two times higher than colchicine. We further investigated the anti-cancer efficacy of compound 3g on human melanoma cells using additional in vitro models, including the wound healing assay and colony formation assay. Compound 3g inhibited colony formation by up to 62.5% and reduced the migration potential of melanoma cells by 69%. The in silico studies reveal the probable interactions with the colchicine binding sites that have a comparable pose to colchicine. 3g formed a hydrogen bond with Cys241, Asn258 and a salt bridge with Lys352, which is important for its tubulin polymerization inhibitory activity. These findings suggest that 3g could selectively target melanoma cells, minimizing toxicity to healthy cells and potentially providing a safer and more effective treatment option with improved therapeutic outcomes.